Musical expertise modulates embodied processing of biological motion and audiovisual-motor integration in rhythmic hand tapping - Alice Mado Proverbio; Matteo Valtolina (NeuroImage)
Musical training enhances sensorimotor integration and multimodal processing, particularly in rhythm perception and execution. However, the neural mechanisms underlying the audiovisual-motor integration of non-musical rhythmic gestures remain poorly understood. This study investigated differences between professional musicians and musically untrained individuals in processing audiovisual rhythmic incongruence, focusing on the anterior error-related negativity (ERN) and the preceding posterior P300 as neurophysiological markers of sensitivity to audio-visuomotor misalignment. We recorded EEG responses from 29 participants (15 musicians, 14 controls) while they observed video recordings of finger tapping synchronized or desynchronized with percussive sounds. Stimuli varied in rhythmic complexity and frequency. Musicians significantly outperformed controls in an independent rhythmic ability test, demonstrating superior auditory-motor encoding. ERP analysis revealed a larger P300 and ERN amplitude for incongruent stimuli, with musicians exhibiting stronger differentiation between conditions. Source localization indicated distinct neural substrates: while non-musicians primarily engaged visual areas, musicians recruited the superior frontal gyrus (BA 10), basal ganglia, and cingulate cortex—structures implicated in rhythmic motor coordination and error monitoring. These findings suggest that musical expertise facilitates embodied cognition of rhythm, refining the integration of auditory, visual, and motor representations. Enhanced activation in prefrontal and subcortical networks in musicians highlights their heightened sensitivity to audiovisual rhythmic discrepancies, underscoring the role of training-induced neuroplasticity in multimodal temporal processing.